2018
DOI: 10.1002/2017ja024811
|View full text |Cite
|
Sign up to set email alerts
|

Annual Occurrence Rates of Ionospheric Polar Cap Patches Observed Using Swarm

Abstract: Dense, fast‐moving regions of ionization called polar cap patches are known to occur in the high‐latitude F region ionosphere. Patches are widely believed to be caused by convection of dense, sunlit plasma into a dark and therefore low‐density polar cap ionosphere. This leads to the belief that patches are a winter phenomenon. Surprisingly, a long‐term analysis of 3 years of ionospheric measurements from the Swarm satellites shows that large density enhancements occur far more frequently in local summer than l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 27 publications
8
51
1
Order By: Relevance
“…Our result shown in Fig. 6 reveals that in both hemispheres the GPS signal losses have a higher occurrence during December solstice, supporting the conclusion of Noja et al (2013) and Chartier et al (2018) that the polar patches have higher occurrence at this season. The possible reason for explaining the different seasonal dependence of polar patches is that Spicher et al (2017) used a method with relative threshold for identifying polar patches (the enhancement must be at least twice that of the background density), while the detection approach used by Noja et al (2013) was based on a mixture of absolute and relative patch magnitudes (besides the relative enhancement, the absolute TEC enhancement must be larger than 4 TECU; 1 TECU = 10 16 electrons m −2 ).…”
Section: Seasonal Dependence Of Gps Signal Losssupporting
confidence: 78%
See 1 more Smart Citation
“…Our result shown in Fig. 6 reveals that in both hemispheres the GPS signal losses have a higher occurrence during December solstice, supporting the conclusion of Noja et al (2013) and Chartier et al (2018) that the polar patches have higher occurrence at this season. The possible reason for explaining the different seasonal dependence of polar patches is that Spicher et al (2017) used a method with relative threshold for identifying polar patches (the enhancement must be at least twice that of the background density), while the detection approach used by Noja et al (2013) was based on a mixture of absolute and relative patch magnitudes (besides the relative enhancement, the absolute TEC enhancement must be larger than 4 TECU; 1 TECU = 10 16 electrons m −2 ).…”
Section: Seasonal Dependence Of Gps Signal Losssupporting
confidence: 78%
“…However, the seasonal dependence of polar patches is still an open issue: some studies reported that the polar patches are mainly a local winter phenomenon in both hemispheres (e.g., Coley and Heelis, 1998;Kivanç and Heelis, 1998;Carlson, 2012;Spicher et al, 2017), while there are also studies found that polar patches have higher occurrence during December solstice months in both hemispheres (e.g., Noja et al, 2013;Chartier et al, 2018). Our result shown in Fig.…”
Section: Seasonal Dependence Of Gps Signal Losssupporting
confidence: 71%
“…Given that sporadic F region enhancements are made up of photoionized plasma convected into the polar caps from the subauroral dayside (e.g., Carlson, ), the well‐known global annual asymmetry (e.g.,Mendillo et al, ; Rishbeth & Müller‐Wodarg , ) also plays an important role in driving the observed pattern of variability, as it controls plasma levels in the supply region. These factors combine in SAMI3 to reproduce the pattern of variability observed here and by Noja et al () and Chartier et al (), with Δ N (as characterized by the range of TEC values present in the polar cap) larger in January than in July in both hemispheres.…”
Section: Discussionsupporting
confidence: 78%
“…Notable observations that appear to support that theory include Coley and Heelis () and Spicher et al (), who counted more F region density spikes in local winter in each hemisphere. Chartier et al () explained that the apparent contradiction between Noja et al () and the others is the result of different counting metrics: Noja et al () tested for a proxy of Δ N (topside TEC enhancements >4 TECU) , whereas the typical approach has been to look for changes in Δ N / N , expressed perhaps most famously in Crowley's () test specifying that a patch must be greater than twice the background density. This choice of a different metric explains why Noja et al () got a different result than the others, but it does not explain why Δ N should have an annual variability with a marked minimum in July.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies in which the in situ electron density measurements from the CHAMP and SWARM satellite systems have been used to compare the morphology and frequency of patch occurrence in the Northern and Southern Hemispheres include Noja et al () and Chartier et al (). The results reported in these two studies are distinctly different from those we obtain here in the present study; both conclude that patches in both hemispheres occur most frequently during the same months of the year, and not in each hemisphere's winter months.…”
Section: Introductionmentioning
confidence: 99%